Untimely Laws, Criminal Code and Images of the Simony - Gómez de Maya, Julián (Historia, instituciones, documentos, 2018)
La superación del Antiguo Régimen se resuelve en un complejo, poliédrico proceso pleno de facetas y aristas. La legislación contra el crimen de simonía, verbigracia, penetra en el siglo XIX sostenida aún dentro del ordenamiento español; por supuesto, la tendencia laicizadora que característicamente opera en el proceso codificador supondrá el retraimiento en su represión, pero de alguna manera, entre tradición y reformismo, su objeto quintaesenciado va a buscar otras formas acreedoras al interés punitivo del Estado liberal: los nombramientos ilegales mediante cohecho.The overcoming of the Old Regime is resolved in a complex, polyhedral process full of facets and edges. The legislation against the crime of simony, for example, penetrates into the 19th century still sustained within the Spanish legal system; of course, the laicizing tendency that characteristically operates in the codifying process will suppose the retreat in its repression, but in some way, between tradition and reformism, its quintessential object was going to look for other forms that are worthy of the punitive interest of the liberal State: illegal appointments through bribery.Fundación Séneca 19208/PI/1